PENGARUH PEMBERIAN ZINK TERHADAP JUMLAH SEL LEYDIG PADA TESTIS MENCIT (MUS MUSCULUS) YANG DIINDUKSI SIKLOFOSFAMID - Estu Adil Prasetyo (2021)
This research aims to determine the effect of zinc on the number of leydig cells in the mice testes (Mus musculus) induced by cyclophosphamide. This research uses post control group design only with male mice divided by 6 groups. The first group (K1), negative control, not induced zinc or cyclophosphamide. The second (K2) injected cyclophosphamide 200 mg/KgBW/day. The third (K3) injected zinc 100 mg/KgBW/day. The fourth (K4), fifth (K5), and sixth (K6) groups were given cyclophosphamide with same dose and zinc at different doses. K4 is administered zinc 25 mg/KgBW/day. K5 with zinc 50 mg/KgBW/day. K6 with zinc 100 mg/KgBW/day. All treated for 33 days. The mice dissected and take the testicle. Furthermore, making histological preparations using HE staining, then do calculation of the number of leydig cells. Variance analysis data using One Way ANOVA and Benferroni post hoc test. The results showed there was significant influence (p<0.05) of zinc administration for increase the number of testicular leydig cells after induced by cyclophosphamide. The number of leydig cells in K2 increased significantly compared to K6 (P<0.05). The conclusion is zinc had a significant effect for increase the number of leydig cells in the mice testes (Mus musculus) induced by cyclophosphamide.